Identification of Butterfly Larval Host Plants in the Taman Wisata Alam (TWA) Gunung Tunak, Central Lombok - Jupri, Ahmad; Cahyani, Inda Nur; Supardiono, Supardiono; Hidayati, Lilik (Jurnal Biologi Tropis, 2025)
Host plants play an important role in the survival of butterflies, especially in the larval phase which is highly dependent on certain types of plants to obtain nutrients and essential chemicals. Various efforts need to be made to preserve the diversity of butterflies in the Gunung Tunak TWA Area through identification of butterfly larval host plants. This study was conducted to identify the diversity of butterfly larval host plants in the Gunung Tunak Nature Tourism Park, Central Lombok, NTB. Data collection was carried out using the exploration method for four days in two main locations, namely the breeding area and the observation route. The identification results found seven species of host plants, namely Pagoda (Clerodendrum japonicum), Biduri (Calotropis gigantea), Beringin (Ficus hispida), Aristukia (Aristolochia tagala), Bunga Air Mata Pengantin (Antigonon leptopus), Jeruk Purut (Citrus hystrix), and Jeruk Lemon (Citrus limon). Four of the seven plants found are hosts for butterfly larvae of the Nymphalidae family. Aristukia plants were only found in limited numbers, which may affect the survival of the protected butterfly species, Troides helena. These results emphasize the importance of conserving host plants to support the sustainability of butterfly populations in this area.